Screening for suicidality in cancer patients using Item 9 of the nine-item patient health questionnaire; does the item score predict who requires further assessment? - Walker, J; Hansen, C; Hodges, L; Thekkumpurath, P; O'Connor, M; Sharma, N; Kleiboer, A; Murray, G; Kroenke, K; Sharpe, M (2010)
OBJECTIVE: To determine whether a higher score on Item 9 of the Patient Health Questionnaire-9 (range zero to three) was more likely to indicate suicidality as determined at subsequent clinical interview in cancer outpatients. METHOD: Analysis of anonymized data (with ethical approval) obtained from the routine clinical administration of self-report questionnaires and telephone interviews to patients attending a cancer centre in the UK. RESULTS: Complete data were available on 330 patients. Those with higher scores on the item were more likely to be suicidal at interview. However, a substantial number of those (54/235; 23%) who scored only one on the item were also found to be suicidal. CONCLUSIONS: A higher score on Item 9 of the PHQ-9 indicates a greater likelihood that the patient is suicidal. However, even patients who score only 1 may be suicidal and consequently also require further assessment.